2020
DOI: 10.1177/0730888420983396
|View full text |Cite
|
Sign up to set email alerts
|

Creating “Risky” New Roles in Healthcare: Identities, Boundary-Making, and Skilling Under Rationalization and Consumer Demand

Abstract: Healthcare is experiencing two countervailing pressures: to increase efficiency and be more responsive to consumer demands. Healthcare organizations often create new work arrangements, including “lay healthcare” roles, to respond to these pressures. Using longitudinal qualitative data, this article analyzes how one set of new lay healthcare workers attempted to construct a workplace identity, sell their value to existing professional workers, and navigate the precarious conditions of the new role. The authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Even though new roles are sometimes not well accepted by existing staff in the team, 11,[13][14][15][16] and established hierarchies can be a barrier to their implementation, 1 the satisfaction survey shows that physicians are satisfied with the new role introduction. They particularly appreciate the reduction in consultation time and the improvement in the quality of consultations, and that this reduction in time spent on administrative tasks allows them to devote themselves to other care activities, as well as to research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though new roles are sometimes not well accepted by existing staff in the team, 11,[13][14][15][16] and established hierarchies can be a barrier to their implementation, 1 the satisfaction survey shows that physicians are satisfied with the new role introduction. They particularly appreciate the reduction in consultation time and the improvement in the quality of consultations, and that this reduction in time spent on administrative tasks allows them to devote themselves to other care activities, as well as to research.…”
Section: Discussionmentioning
confidence: 99%
“…1 Several studies notice that new roles are not always well accepted by existing staff in the team. 11,[13][14][15][16] Other research show the payment system is identified as another potential barrier to task shifting, for instance, if reimbursement is only possible when a procedure is done by a concrete category of health worker. 17 Task shifting in Europe has been majorly centered in the growth of tasks assumed by nurses that were formerly performed by physicians.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of this context on delivery is perhaps unsurprising. Community health workers in the United States, for instance, have previously described how the ‘agenda less’ relationships they built with clients were undermined by embedded neoliberal health‐care structures and targets (Cain et al., 2021 , pp. 353–385) that commonly align with a logic of choice (Mol, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though new roles are sometimes not well accepted by existing staff in the team [14,18,[19][20][21], a satisfaction survey conducted specifically in the oncology department shows that physicians are satisfied with the new role introduction. Physicians particularly appreciate the reduction in consultation time and the improvement in the quality of consultations, and that this reduction in time spent on administrative tasks allows them to devote themselves to other care activities, as well as to research.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical assistants made 13,553 requests in the outpatient area, which represents 69.93% of the total number of requests subject to the study period (19,381). Table 1 breaks down the administrative activity of the outpatient area according to the types of requests and their corresponding time spent.…”
Section: Types Of Requests Madementioning
confidence: 99%